Total shoulder arthroplasty: risk factors for a prolonged length of stay. A retrospective cohort study. Issue 6 (November 2019) - Hartwell, Matthew J.; Nelson, Patrick; Johnson, Daniel J.; Nicolay, Richard W.; Christian, Robert A.; Selley, Ryan S.; Terry, Michael A.; Tjong, Vehniah K.
Abstract : Background: Recent studies describe safe outcomes for outpatient total shoulder arthroplasty. This study identifies risk factors for hospital admissions exceeding 24 hr. Methods: The National Surgical Quality Improvement Program database was queried for billing codes related to total shoulder arthroplasty. Patients were grouped according to length of stay, ⩽24 hr or >24 hr. Univariate and multivariate analyses were used to identify patient demographics, preoperative comorbidities, and intraoperative risk factors for prolonged hospitalizations. Results: Of the 14, 339 patients who met the inclusion criteria, 6, 507 patients (45.3%) had a length of stay ⩽24 hr. Multivariate analysis identified age (odds ratio [OR], 1.03; 95% confidence interval [CI], 1.02-1.03), American Society of Anesthesiology classification (OR, 1.5; 95% CI, 1.4-1.6), diabetes (OR, 1.7; 95% CI, 1.4-2.0), chronic obstructive pulmonary disease (OR, 1.4; 95% CI, 1.2-1.6), congestive heart failure (OR, 2.7; 95% CI, 1.3-5.3), dialysis (OR, 2.5; 95% CI, 1.3, 4.8), history of a bleeding disorder (OR, 1.5; 95% CI, 1.2-1.9), and operative time (OR, 1.01; 95% CI, 1.01-1.01) as risk factors for prolonged hospitalization. Male gender was a protective factor for prolonged hospitalization (OR, 0.50; 95% CI, 0.46-0.53). Conclusions: Female gender, increasing age, American Society of Anesthesiology classification, operative time, or a history of diabetes, chronic obstructive pulmonary disease, congestive heart failure, or a bleeding disorder are risk factors for prolonged hospitalization following total shoulder arthroplasty. Level of Evidence: Level III.